Preparation and Characterization of an Optimized Meniscal Extracellular Matrix Scaffold for Meniscus Transplantation - He, Yong; Chen, Yunbin; Wan, Xinyu; Zhao, Chenchen; Qiu, Pengcheng; Lin, Xianfeng; Zhang, Jianfeng; Huang, Yue (Frontiers in Bioengineering and Biotechnology, 2020)
Many studies have sought to construct a substitute to partially replace irreparably damaged meniscus. Only the meniscus allograft has been used in clinical practice as a useful substitute, and there are concerns about its longevity and inherent limitations, including availability of donor tissue and possibility of disease transmission. To overcome these limitations, we developed an acellular xenograft from whole porcine meniscus. Samples were treated with 2% Triton X-100 for 10 days and 2% sodium dodecyl sulfate for 6 days. The DNA content of extracellular matrix (ECM) scaffolds was significantly decreased compared with that of normal porcine menisci (p < 0.001). Histological analysis confirmed the maintenance of ECM integrity and anisotropic architecture in the absence of nuclei. Biochemical and biomechanical assays of the scaffolds indicated the preservation of collagen (p = 0.806), glycosaminoglycan (p = 0.188), and biomechanical properties (elastic modulus and transition stress). The scaffolds possessed good biocompatibility and supported bone marrow mesenchymal stem cells (BMSCs) proliferation for 2 weeks in vitro, with excellent region-specific recellularization in vivo. The novel scaffold has potential value for application in recellularization and transplantation strategies.